Investigation of dynamic wind loads on a long-span suspension bridge identified from measured acceleration data. Issue 196 (January 2020) - Petersen, Ø.W.; Øiseth, O.; Lourens, E.
Abstract: The traditional wind load assessment for long-span bridges relies on assumed models for the wind field and aerodynamic coefficients from wind tunnel tests, which usually introduce some uncertainties. Recent studies have shown that large deviations can exist between the predicted and observed wind-induced dynamic response of suspension bridges. In studies of the dynamical behavior of bridges, inverse force identification methods can therefore be an interesting tool in the assessment of possible uncertainties involved in the modeling of wind loads. This paper presents a novel case study of the identification of the dynamic wind loads on the 1310 ​m long Hardanger bridge, a suspension bridge equipped with a monitoring system for wind and vibrations. The modal wind loads are identified from acceleration data using an algorithm for model-based joint input and state estimation. Several data sets with different wind conditions are presented. The wind loads are studied in the time and frequency domains and are compared to the mean velocity and turbulence characteristics of the wind. Highlights: Wind loads on bridges can be inversely identified from acceleration data. A case study on estimation of wind loads on the Hardanger bridge is presented. The wind loads are examined in the time and frequency domain. The time evolution of the wind loads shows correspondence with the turbulence.